2008
DOI: 10.1016/j.cie.2008.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Single-machine scheduling with periodic and flexible periodic maintenance to minimize maximum tardiness

Abstract: This paper considers a single machine scheduling problem with several maintenances periods. Specically, two situations are investigated. In the rst one, maintenance periods are periodically xed: maintenance is required after a periodic time interval. In the second one, the maintenance is not xed but the maximum continuous working time of the machine which is allowed is determined. The objective is to minimize the maximum tardiness. These problems are known to be strongly NP-hard. We propose some dominance prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(43 citation statements)
references
References 16 publications
0
43
0
Order By: Relevance
“…Processing times, p, are randomly chosen from a discrete uniform distribution over [1; 10], identically done in some other references, e.g. Sbihi and Varnier [17], Liao and Chen [8], and Pathumnakul and Egbelu [23]. For any problem with n jobs, we run 10 random sampling (replications) for each combination of parameters.…”
Section: Numerical Examples and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Processing times, p, are randomly chosen from a discrete uniform distribution over [1; 10], identically done in some other references, e.g. Sbihi and Varnier [17], Liao and Chen [8], and Pathumnakul and Egbelu [23]. For any problem with n jobs, we run 10 random sampling (replications) for each combination of parameters.…”
Section: Numerical Examples and Resultsmentioning
confidence: 99%
“…They showed that these problems are NP-hard. Sbihi and Varnier [17] presented a heuristic method for the single-machine scheduling problem with several maintenance periods. Speci cally, two situations were investigated in their study: rst, maintenance periods were periodically xed (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…As periodic maintenance predetermines a fixed time interval to perform maintenance operations (i.e., characteristics of the unavailability periods is known in advance), machine idleness will appear due to the incoordination of the total processing time of prior batch and the fixed time interval. Hence, though these research have considered periodic maintenance planning into production scheduling model, it seems not economic due to machine idleness [17][18][19]. If maintenance operations could be well planned according to jobs' processing time and machine's condition, much more resources will be saved.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sbihi and Varnier [18] studied the same problem by using their own proposed model. And the schedule obtained by their model is shown in Fig.…”
Section: Case 2: Production Scheduling Model With Periodic Maintenancmentioning
confidence: 99%
“…In this problem, machines must be stopped for periodical maintenance (Pinedo, 2002, Chen, 2006. Sbihi and Varnier (2008) considered a single-machine scheduling problem with several maintenances periods under two different scenarios. In the first one, maintenance periods were periodically fixed while in the second one, the maintenance was not fixed but the maximum continuous working time of the machine allowed was determined.…”
Section: Introductionmentioning
confidence: 99%